A novel Erbium-doped Fiber Laser source (EDFL) - Sellami , Ali; Al-Khateeb, Khalid A. Saeed; Billoui, Bouzid (2008)
A novel configuration of a new erbium doped fiber laser (EDFL) is constructed and analyzed. It utilizes embedded fiber-loop mirrors, tunable filters with a linear laser oscillation. Implementing the linear cavity fiber loop (LCFL) as a new configuration using three circulators and two tunable band-pass filters (TBF), the output power in the single wavelength (SW) laser was improved. The output power of the proposed laser system is more than 18 dBm at 1560 nm. The side mode suppression ratio (SMSR) in the output power in this experiment was also high, greater than 64 dB. It is found that the double filtering technique in the proposed configuration enables the system to achieve higher power and lower amplified spontaneous emission (ASE) noise levels.